Pengembangan Flipbook Panduan Praktikum Food and Beverage Service Model ADDIE untuk Siswa Perhotelan SMKN 1 Sukasada - Kadek Rismayani; Ni Made Suriani; Cokorda Istri Raka Marsiti (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2026)
This research aims to develop a learning media in the form of a practical guide Flipbook for the Food and Beverage Service subject to determine the feasibility level of the developed product so that it can be applied in the learning process at SMK N 1 Sukasada. The type of research applied is R&D (Research and Development) with the ADDIE model, which includes five stages: Analyze, Design, Development, Implementation, and Evaluation. The research subjects involved content experts, media experts, and field testing with a small group of 10 students from grade XI (Phase F) Hospitality Program at SMK N 1 Sukasada. The validation results show that the assessment by content experts obtained a percentage of 97.5% categorized as "Highly Feasible," the media experts’ assessment obtained 97% categorized as "Highly Feasible," and the small group test results obtained 90.5% categorized as "Highly Feasible." Based on these results, the learning media in the form of a practical guide Flipbook for the Food and Beverage Service subject is declared highly feasible for use in the learning process for Phase F students in the Hospitality Program at SMK N 1 Sukasada.